Assessment of Clinical Research Outcomes for Personalizing Nicotinamide Riboside Dosing. (29th May 2020) - Idoine, Rebecca; Erickson, Aron; Shao, Andrew; Ishtiaq, Yusrah; Roberts, Matthew; Nkrumah-Elie, Yasmeen
Abstract: Objectives: Introduction: Nicotinamide riboside (NR), is a NAD + precursor that is commercially available as a nutritional supplement. NAD + levels have been shown to decline in older adults, thus NR has been identified as a healthy aging nutritional supplement. Clinical and preclinical studies have demonstrated the safety and efficacy of NR supplementation at various doses, however individual responsiveness have been minimally reported. As individuals differ in multiple parameters that may result in variations in response to supplementation, dosing personalization may be a key to NR supplement effectiveness. Objective: Determine if published data of clinical NR supplementation can be used to personalize NR dosing. Methods: A meta-analysis of published clinical trials of NR supplementation was conducted. Included studies were limited to those that were exclusive to NR supplementation with multiple doses for at least one week. The assessment compared NR dosing, study population demographics, changes in NAD levels, adverse effects, and study outcomes. Results: A total of 11 publications report clinical results from NR supplementation demonstrated in 9 clinical trials (4 RCT), however only five of the studies met our criteria. Most of the studies have been conducted in both males and females with an average age of 45–65 years, with various BMIs. Dosing ranged from 100 mg/day to 2000 mg/day, for a duration of 9 days to 3 months, with no major adverse events reported. When measured, NAD + levels were shown to increase by as much as 139% with 1000 mg/day of NR for 56 days. Measurements for changes in NAD + lacked standardization in collection, analysis, and reporting, thus parallel comparisons could not be made. Additionally, studies did not separate NR responses based upon gender, age, BMI, and health status, preventing personalization of the available data. Conclusions: To effectively personalize NR dosing, standardization of NAD + analyses and clinical outcomes is gravely needed. Future use of phenotypic flexibility approaches may be beneficial in demonstrating the clinical benefits of NR supplementation. Lastly, it is recommended that future studies include heterogenous response study outcomes to identify responders/non-responders to various endpoints following NR supplementation. Funding Sources: None.